1937
DOI: 10.1111/j.1469-185x.1937.tb01231.x
|View full text |Cite
|
Sign up to set email alerts
|

The Specificity and Collaboration of Digestive Enzymes in Metazoa

Abstract: Summary The identity of the digestive enzymes found in vertebrates and invertebrates has been discussed. For the proteases the conclusion is reached that in the vertebrates as well as in the invertebrates (as far as investigated) the protein molecule is attacked by at least four different enzymes, a proteinase, carboxypolypeptidase, aminopolypeptidase and dipeptidase, which can be separated by adsorption. (Recent researches have, moreover, demonstrated the presence of a separate protaminase in the former t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

1938
1938
2008
2008

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 175 publications
0
4
0
2
Order By: Relevance
“…In general, pepsinogen is found in all vertebrates except the stomachless fish (Vonk 1973). So far, no acid digestive proteinases from the digestive tract of the stomachless species have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, pepsinogen is found in all vertebrates except the stomachless fish (Vonk 1973). So far, no acid digestive proteinases from the digestive tract of the stomachless species have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…5). The alkaline proteinase widely existed in pancreas and the intestine of the vertebrate (Vonk 1973). Einarsson & Davis (1996) studied the ultrastructure of the secreting cell which excreted trypsin and chymotrypsin, and reported that these cells existed plentifully in the alimentary canal of Atlantic salmon.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it can be safely construed that as in Locusta migratoria and Dysdercus fasciatus (KHAN, 1962) there is no serial localization of proteotytic enzymes in the digestive tract. Therefore, the concept of a "ferment chain" as it occurs in vertebrates (VoNK, 1937) La distribution de l'activit~ de dipeptidase a 6t6 6tudi~e dans diff6rentes r6gions du tube digestif de Utetheisa pulchella L. b. l'aide de la chromatographie b. papier (m&hode semi-quantitative). Les dipeptidases, capables d'hydroliser les L-alanylglycine et L-leucylglycine se rencorttrent dans l'extrait de la glande salivaire, des tissus de l'intestin moyen et le contenu de la lumi6re de l'intestin moyen.…”
Section: Resultsunclassified
“…ant&ieure, moyenne ou post&ieure) de l'intestin moyen. La th~,se d'une ,chaine de ferment,, tel qu'il existe chez les vert~bres (Vonk, 1937) et chez Periplaneta orientalis (Schlottke, 1937c) n'est done pas soutenue par les observations sur U. pulchella.…”
Section: Resultsunclassified
“…After the early works of Vonk (1937), a great number of papers have been focused to the study of amylase activity in fresh water and marine fish (Keddis 1957; Fish 1960; Ushiyama et al . 1965; Ugwumba 1993; Hidalgo et al .…”
Section: Introductionmentioning
confidence: 99%